Corrective and Reconstructive Surgery of Various Trauma of Head Region in Dogs - Parmar, Jignesh J.; Shah, Nisarg; Vaishnav, Hariom; Shah, Aaditya I.; Rao , Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Five male dogs age ranging from 2 to 7 years, were presented in emergency services at Veterinary Clinical Complex of the College in Anand with the history of traumatic injuries of different grades on ear and head region following automobile accidents. The physiological parameters were within normal range in 3 cases, whereas increased heart and respiration rates and rectal temperature were observed in 2 dogs. All dogs were treated under general anaesthesia with either simple suturing or reconstructive surgery. Four dogs recovered well without any complications, whereas one dog which died suddenly without any sign.